2007
DOI: 10.1213/01.ane.0000261256.88414.e4
|View full text |Cite
|
Sign up to set email alerts
|

The Coagulation Changes Induced by Rapid In Vivo Crystalloid Infusion Are Attenuated When Magnesium Is Kept at the Upper Limit of Normal

Abstract: Rapid hemodilution-induced coagulation may be partially due to decreased magnesium, and the effect is attenuated by maintaining magnesium at the upper limit of normal. Crystalloid resuscitation fluids should possibly contain higher magnesium levels, around 3 mmol/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
1
21
0
2
Order By: Relevance
“…It is worth noting that some authors observed hypercoagulation following crystalloid infusion. 20,21 A rapid infusion of crystalloids increases coagulative activity following hemodilution in healthy volunteers. 20 In vitro studies also document an increase in hypercoagulation measured by thrombelastography following different types of crystalloids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that some authors observed hypercoagulation following crystalloid infusion. 20,21 A rapid infusion of crystalloids increases coagulative activity following hemodilution in healthy volunteers. 20 In vitro studies also document an increase in hypercoagulation measured by thrombelastography following different types of crystalloids.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 A rapid infusion of crystalloids increases coagulative activity following hemodilution in healthy volunteers. 20 In vitro studies also document an increase in hypercoagulation measured by thrombelastography following different types of crystalloids. 21,22 Interestingly, this effect seems to depend on blood magnesium concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proved that in situation of rapid IV fluid infusion, maintaining the magnesium at the upper limit of normal value attenuates rapid hemodilution-induced coagulation change due to decreased magnesium level in healthy volunteers. 7 There were also some studies that magnesium interrupted platelet aggregation and adhesion so magnesium sulphate administration induced hypo coagulation state. 8,9 The aim of the present study was to determine the serum may level three days postoperatively in Mitral valve repair and replacement surgeries.…”
Section: Magnesium May Influence the Incidence Of Cardiac Arrhythmiasmentioning
confidence: 99%
“…Crystalloids, colloids, and starch solutions briefly dilute coagulation precursors and enzymes, alter blood turbulence, and exaggerate blood pressure, which conveys the misleading impression that they improve cardiac output [384,687,688]. DIC removes red cells from circulation, causing anemia that exaggerates blood turbulence and inhibits coagulation [457].…”
Section: Disseminated Intravascular Coagulation (Dic)mentioning
confidence: 99%